Ayu Lucy Larassaty PENGARUH FAKTOR INTERNAL DAN EXTERNAL TERHADAP KINERJA DOSEN DI UNIVERSITAS NAHDLATUL ULAMA SIDOARJO : Program Studi Manajemen, Universitas Nahdlatul Ulama Sidoarjo *e-mail: larassaty46@gmail.com - Ayu Lucy Larassaty (GREENOMIKA, 2019)
The research has the aim to find out the influence of internal and external factors on the performance of lecturers at the Nahdlatul Ulama Sidoarjo University in order to be able to bring up students who can compete with the challenges of the global world. This research uses quantitative research methods and data processing is done by eviews software. The results showed that internal factors influenced lecturer performance. External factors affect the performance of lecturers. Internal and external factors affect together the lecturer performance.